Formación integral en la calidad del servicio PAAI en la USTA Tunja (2018)
The article presented below is an analytical-descriptive-documentary review thatdeals, firstly, with the concepts of integral formation, later, the integration of such concepts in the PEI (Institutional Education Project) and the Institutional Academic Accompaniment Program (PAAI) of the Universidad Santo Tomás Tunja Sectional, and finally, with the experiences in the measurement of the quality of higher education. It looks at this in a context in which quality and integral training have become obligations rather than advantages for educational institutions, whose work must be oriented to contributing to the formation of people apt to work with knowledge, but that in addition are capable of achieving their self-realization andof contributing to the well-being of the community in which they are immersed.